Altered Brain Signal Variability in Patients With Generalized Anxiety Disorder - Li, Liyuan; Wang, YiFeng; Ye, Liangkai; Chen, Wang; Huang, Xinju; Cui, Qian; He, Zongling; Liu, Dongfeng; Chen, Huafu (Frontiers in Psychiatry, 2019)
Generalized anxiety disorder (GAD) is characterized by chronic, continuous symptom of worry and exaggerated startle response. Although functional abnormality in GAD has been widely studied using functional magnetic resonance imaging (fMRI), the dynamic signatures of GAD are not fully understood. As a vital index of brain function, brain signal variability (BSV) reflects the capacity of state transition of neural activities. In this study, we recruited 47 patients with GAD and 38 healthy controls (HCs) to investigate whether or not BSV is altered in patients with GAD by measuring the standard deviation of fMRI signal of each voxel. We found that patients with GAD exhibited decreased BSV in widespread regions including the visual network, sensorimotor network, frontoparietal network, limbic system, and thalamus, indicating an inflexible brain state transfer pattern in these systems. Furthermore, the correlation between BSV and trait anxiety score was prone to be positive in patients with GAD but negative in HCs. The opposite relationships between BSV and anxiety level in the two groups indicate that the brain with moderate anxiety level may stay in the most stable rather than in the flexible state. As the first study of BSV in GAD, we revealed extensively decreased BSV in patients with GAD similar to that in other mental disorders but with a nonlinear relationship between BSV and anxiety level indicating a novel neurodynamic mechanism of the anxious brain.